Risk of Myocardial Infarction in Inflammatory Bowel Disease: A Population-based National Study. Issue 6 (30th November 2018) - Panhwar, Muhammad Siyab; Mansoor, Emad; Al-Kindi, Sadeer G; Sinh, Preetika; Katz, Jeffry; Oliveira, Guilherme H; Cooper, Gregory S; Ginwalla, Mahazarin
Abstract: Background & Objective: Chronic inflammation is linked to increased cardiovascular risk. Inflammatory bowel disease (IBD) is characterized by chronic inflammation of the gastrointestinal tract and elevated pro-inflammatory markers. The association between IBD and myocardial infarction (MI) is not well understood. We sought to elucidate this risk using a large database. Methods: We reviewed data from a large commercial database (Explorys, IBM Watson) that aggregates electronic medical records from 26 nationwide health care systems. Using systemized nomenclature of medicine-clinical terms, we identified adult patients (20 to 65 years) with a diagnosis of IBD—ulcerative colitis (UC) or Crohn's disease (CD)—who had active records between August 2013 and August 2018. We then examined the risk of MI in patients with or without IBD. Results: Out of 29, 090, 220 patients, 131, 680 (0.45%) had UC, and 158, 750 (0.55%) had CD. Prevalence of MI was higher in patients with UC and CD versus non-IBD patients (UC 6.7% vs CD 8.8% vs non-IBD 3.3%, odds ratio [OR] for UC 2.09 [2.04 -2.13], and CD 2.79 [2.74–2.85]. The odds of MI in IBD patients overall were highest in younger patients and decreased with age (age 30–34 years: OR 12.05 [11.16–13.01], age 65+ years: OR 2.08 [2.04–2.11]). After adjusting for age, race, sex, and traditional cardiovascular risk factor, IBD conferred greater odds of MI (adjusted odds ratio [aOR] 1.25 [1.24–1.27]). Conclusion: In this large cohort, IBD is associated with significantly increased MI compared with non-IBD patients. The relative risk of MI was highest in younger patients and decreased with age. These findings emphasize the need for aggressive risk factor reduction in IBD. Video Abstract: